Relationship between Carlifornia bearing ratio and bearing capacity [electronic resource] - Mohd. Arif Hakimi Mat Hassan, 1988- (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2011